AMICO galaxy clusters in KiDS-DR3: weak lensing mass calibration - Bellagamba, Fabio; Maturi, Matteo (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. We present the mass calibration for galaxy clusters detected with the AMICO code in KiDS DR3 data. The cluster sample comprises 7000 objects and cove
Advance access publication 2019 January 16
Gesehen am 08.05.2019